Pendapat Hukum (Advisory Opinion) Mahkamah Internasional dalam Proses Penyelesaian Sengketa Internasional - Darwiansyah, Mochammad Afief; Luthfi, Muhammad; Aisyah, Nadita Amalia Putri (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
As one of the main courts of the United Nations, the International Court of Justice (ICJ) has the authority to resolve disputes between UN member states or other international institutions. In resolving these international disputes, the ICJ can issue a legal decision in the form of an opinion known as an advisory opinion or legal opinion. Based on this, the author is then interested in formulating a problem regarding the position and nature of legal opinions (advisory opinion) in the process of resolving international disputes. Using the literature study research method, it can be concluded that the legal opinion issued by the ICJ is advisory in nature which does not have binding force and its implementation cannot be enforced.